2004
DOI: 10.1192/pb.28.6.201
|View full text |Cite
|
Sign up to set email alerts
|

Female psychiatrists' career development after flexible training

Abstract: Aims and MethodThe project gathered data from a cohort of 300 flexibly trained female consultants in psychiatry in order to understand how their careers had progressed since the completion of their training. A postal questionnaire was used to gather this information.ResultsThese consultants were generally satisfied with their training, and were succeeding in pursuing their careers. Flexible training was developed to enable people with family commitments to train in psychiatry, and this is what it is being used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Current job provision suggests that not all trainees will achieve this desired outcome and it is possible some will change their view on this as they approach the end of their training. A study of 300 female psychiatrists who had been flexible trainees (Mears et al, 2004) reported that less than a half (43%) had moved into full-time posts, with 73% reporting they had achieved their first choice of working pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Current job provision suggests that not all trainees will achieve this desired outcome and it is possible some will change their view on this as they approach the end of their training. A study of 300 female psychiatrists who had been flexible trainees (Mears et al, 2004) reported that less than a half (43%) had moved into full-time posts, with 73% reporting they had achieved their first choice of working pattern.…”
Section: Discussionmentioning
confidence: 99%